Validity of two general outcome measures of science and social studies achievement - Mooney, Paul; Lastrapes, Renée E.; Marcotte, Amanda M.; Matthews, Amy (Special Education, 2016)
The present research expanded validity findings for a structured formative assessment measure of content learning that was administered online and known as critical content monitoring. The study also evaluated the potential for additional measures, including sentence verification technique and written retell, to explain variance in student achievement in science and social studies classrooms. Participants were fifth-grade students (N=51) enrolled in a public primary school in the southeastern U.S. Three predictor variables (i.e. critical content monitoring, sentence verification technique and written retell) were correlated with content test scores from the nationally representative standardized achievement test (i.e. Stanford Achievement Test-Tenth Edition abbreviated online form) and a statewide accountability test. Pearson correlations for critical content monitoring and the Stanford tests across science (r=.55) and social studies (r=.63) were moderately strong and similar in magnitude with other reported correlations for academic language measures in the literature. Correlations for critical content monitoring were descriptively larger than those between the standardized tests and sentence verification technique and written retell. Commonality analyses indicated that both critical content monitoring and sentence verification technique added unique variance to explanatory models. Limitations and implications were discussed.